2020
DOI: 10.1051/0004-6361/201936935
|View full text |Cite
|
Sign up to set email alerts
|

The spatial evolution of young massive clusters

Abstract: Context. Better understanding of star formation in clusters with high-mass stars requires rigorous dynamical and spatial analyses of star-forming regions. Aims. We seek to demonstrate that “INDICATE” is a powerful spatial analysis tool which when combined with kinematic data from Gaia DR2 can be used to probe star formation history in a robust way. Methods. We compared the dynamic and spatial distributions of young stellar objects (YSOs) at various evolutionary stages in NGC 2264 using Gaia DR2 proper motion d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 28 publications
4
39
0
Order By: Relevance
“…On this log-log plot (Figure 22, right panel), at angular separations of several arcminutes, the slope for Class I YSOs is significantly flatter than for flat spectrum YSOs, which is also significantly flatter than those for Class II and III YSOs, implying that the earlier stages are more clustered. This finding agrees with numerous other examinations of the spatial distribution of sources by YSO class (e.g., Sung et al 2009;Samal et al 2010;Buckner et al 2020). We note that even some candidate Class I YSOs appear isolated: for example, ∼100 of these objects (<1% of the Class I YSOs) are separated from their nearest neighbors in our catalog by more than 10′.…”
Section: Spatial Distribution Of Ysos By Classsupporting
confidence: 92%
“…On this log-log plot (Figure 22, right panel), at angular separations of several arcminutes, the slope for Class I YSOs is significantly flatter than for flat spectrum YSOs, which is also significantly flatter than those for Class II and III YSOs, implying that the earlier stages are more clustered. This finding agrees with numerous other examinations of the spatial distribution of sources by YSO class (e.g., Sung et al 2009;Samal et al 2010;Buckner et al 2020). We note that even some candidate Class I YSOs appear isolated: for example, ∼100 of these objects (<1% of the Class I YSOs) are separated from their nearest neighbors in our catalog by more than 10′.…”
Section: Spatial Distribution Of Ysos By Classsupporting
confidence: 92%
“…We remind the reader that, since the new group is located behind the molecular cloud complex, we are missing those members that are too extincted to be detected by Gaia DR2. For comparison, regarding the population of NGC 2264, Teixeira et al (2012) calculated a total number of sources of 1436 ± 242, while (Buckner et al 2020) estimate a population of 1795 (differences in the areas surveyed and the wavelength coverage may account for the slightly differing values). The new co-moving group is therefore comparable in population size to NGC 2264.…”
Section: Age and Mass Functionmentioning
confidence: 99%
“…Monoceros OB1's molecular cloud complex is located between 697 pc and 784 pc Zucker et al (2019), and has spawned the NGC 2264 cluster in the east, and a series of reflection nebula (termed Mon R1 by van den Bergh 1966) in the west (see Figure 1). The most well studied cluster in Mon OB1 is NGC 2264 (Dahm 2008, and references therein), (Young et al 2006;Teixeira et al 2006Teixeira et al , 2007Teixeira et al , 2008Forbrich et al 2010;Alencar et al 2010;Kwon et al 2011;Teixeira et al 2012;Mariñas et al 2013;Pineda & Teixeira 2013;Cody et al 2014;Rapson et al 2014;Venuti et al 2014;McGinnis et al 2015;Sousa et al 2016;Tobin et al 2015;Schneider et al 2018;Costado & Alfaro 2018;Venuti et al 2019;Sousa et al 2019;Montillaud et al 2019b,a;Buckner et al 2020;Jackson et al 2020;Pearson et al 2020 (Green et al 2019). The most prominent star-forming region is NGC 2264; it is located within the ellipse representing the approximate area surveyed with Spitzer by Rapson et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…NGC 2264 is not a centrally concentrated cluster, but spatially elongated along a NW-SE orientation with different subclusters spread along ∼8 pc (Tobin et al 2015;Buckner et al 2020). Zwintz et al (2017) suggested a diameter of ∼39 arcmin, which translates to 8-14 pc depending on the distance used to convert from arcmin to parsec.…”
Section: Search Targetmentioning
confidence: 99%